2014
DOI: 10.1007/s10840-014-9903-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiofrequency catheter ablation on left ventricular structure and function in patients with atrial fibrillation: a meta-analysis

Abstract: RFCA in AF patients could reverse LV structural remodeling and improve LV systolic function, especially in patients with low LVEF and chronic AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Several studies have demonstrated significant improvements in LVEF following AF ablation, particularly in patients with no known cause of cardiomyopathy, , although few have sought specifically to evaluate the population with KHD. Hsu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated significant improvements in LVEF following AF ablation, particularly in patients with no known cause of cardiomyopathy, , although few have sought specifically to evaluate the population with KHD. Hsu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated significant improvements in LVEF following AF ablation, particularly in patients with no known cause of cardiomyopathy, 4,5,[18][19][20][21] although few have sought specifically to evaluate the population with KHD. Hsu et al found patients with "concurrent structural heart disease" had significant improvements in LVEF post-ablation although to a significantly lesser extent than those without (16 ± 14% vs. 24 ± 10%, P = 0.007 for comparison).…”
Section: Improvement In Left Ventricular Ejection Fractionmentioning
confidence: 99%
“…As for LV reverse remodeling, Reant et al demonstrated significant improvement of LVEF 1 year after PVI in 48 patients with isolated AF . A recent meta‐analysis including 21 studies (1135 patients) confirmed that catheter ablation for AF improved the LVEF . Further, Kim et al showed significant LV mass reduction in 35 patients without AF recurrence after PVI .…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of AF initiates a vicious cycle propagating further LA and LV remodeling, and consequently worsening of AF . Circumferential PVI is considered a reasonable treatment option for patients with symptomatic drug‐refractory AF, and successful PVI is known to be associated with beneficial effects on LA and LV remodeling. Tops et al showed significant LA size reduction at 3 months after PVI in patients without AF recurrence using echocardiography .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation